2013
DOI: 10.1371/journal.pone.0068808
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Metastatic and Anti-Tumor Growth Effects of Origanum majorana on Highly Metastatic Human Breast Cancer Cells: Inhibition of NFκB Signaling and Reduction of Nitric Oxide Production

Abstract: BackgroundWe have recently reported that Origanum majorana exhibits anticancer activity by promoting cell cycle arrest and apoptosis of the metastatic MDA-MB-231 breast cancer cell line. Here, we extended our study by investigating the effect of O . majorana on the migration, invasion and tumor growth of these cells.ResultsWe demonstrate that non-cytotoxic concentrations of O . majorana significantly inhibited the migration and invasion of the MDA-MB-231 cells as shown by wound-healing and matrigel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 58 publications
(76 reference statements)
4
50
0
2
Order By: Relevance
“…Previous work revealed that O. majorana essential oils exhibited antioxidant, antifungal, antimicrobial and antibacterial activities. Origanum majorana ethanolic extract also showed the antimetastatic and antitumor growth effects on human breast cancer cells . Ethanol extract of O. majorana leaves exhibited an anti‐proliferative effect and high antioxidant activity .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous work revealed that O. majorana essential oils exhibited antioxidant, antifungal, antimicrobial and antibacterial activities. Origanum majorana ethanolic extract also showed the antimetastatic and antitumor growth effects on human breast cancer cells . Ethanol extract of O. majorana leaves exhibited an anti‐proliferative effect and high antioxidant activity .…”
Section: Resultsmentioning
confidence: 97%
“…Origanum majorana ethanolic extract also showed the antimetastatic and antitumor growth effects on human breast cancer cells. 49 Ethanol extract of O. majorana leaves exhibited an anti-proliferative effect and high antioxidant activity. 50 Quantitative analysis of arbutin in O. majorana has been presented.…”
Section: Antioxidant Activitiesmentioning
confidence: 98%
“…Hence, the use of essential oils as a source of potent anticancer compounds has gained a great deal of interest in the field of cancer therapy in recent years. We and others have previously extensively documented the anticancer activities of Origanum majorana ethanolic extract against various types of cancer including breast [17,18], colon [19], and liver [34]. However, to the best of our knowledge, no literature data on the anticancer activity of Origanum majorana essential oil are available.…”
Section: Discussionmentioning
confidence: 99%
“…O. majorana essential oil was also able to partially prevent the ethanol-induced decline in sperm quality, testosterone levels, and the weight of reproductive organs in male rats [2]. Previous studies have reported the potential use of O. majorana ethanolic extract as anticancer agent [10, 11], whereas the tea extract has been shown to have immunostimulant, antigenotoxic and antimutagenic properties [3, 12]. These activities are attributed to the chemical composition, which is characterized as rich in flavonoids and terpenoids [13].…”
Section: Introductionmentioning
confidence: 99%